HEALTHY FOOD SAFETY, LEGISLATION AND THE HACCP CONCEPT IN MONTENEGRO - Vujacic, Vesna; Cerovic, Drazen (European Scientific Journal, ESJ, 2013)
Due to the natural, cultural and historical potentials, development trends and strategic orientation to develop as a tourist destination, tourism in the long term presents one of the biggest potential for economic and business progress of Montenegro. As one of the countries of the Mediterranean ring, Montenegro belongs to that area not only geographical, climatic but tourist as well. With the development of tourism, the imperative is the need to provide for the tourists not only quality but also healthy food, valuing at the same time the internationally recognized standards. It is known that food is a very risky element of tourism, and the HACCP concept is the establishment of food safety systems through the analysis and control of biological, chemical and physical hazards in the entire process, from production of raw materials, production, distribution and consumption of the finished product. The paper presents the views of legal legislation related to the field of food, international ISO standard, ISO 22 000. The aim of this paper is to emphasize the importance of the HACCP concept.